ISI DAN KEBAHASAAN BUKU TEKS BAHASA INDONESIA KELAS VIII SMP KURIKULUM MERDEKA - Reskiyana, Riska; Usman (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This research is a qualitative descriptive study that aims to describe the feasibility of content and language contained in Indonesian Language textbooks for Grade VIII of Junior High School. The data in this study are quotations of sentences that indicate the feasibility of the content and language of the textbook. Data collection was carried out using reading techniques, documentation techniques, and note-taking techniques. Furthermore, data analysis is to identify data, describe, and analyze qualitative data. The results of the study indicate that the feasibility of content in the indicators of the breadth and depth of the textbook includes real-life examples and interactive exercises that make the content relevant and easily accessible. In the indicator of the suitability of the description of the material with the Competency Standards and Learning Archievement, it is structured and comprehensive to build students' language skills through interesting exercises and activities in the textbook. In terms of linguistic feasibility, this textbook uses clear language accompanied by precise definitions to make it easier for students to understand the material.